Vpliv različnih parametrov na trdnostni preračun toplotno obremenjenega žarometa - Wagner, Andrej (Strojniški vestnik, 2006)
Modern headlamps are made from low-cost plastic materials, which are very convenient for modern headlamp design. On the other hand, plastic materials donot withstand high temperatures. This can cause deformations that result in problems with the photometric properties and with the sealing of headlamp. In this article the stress-strain state of a fog lamp from Saturnus avtooprema d.d. caused by thermal loads was analyzed with finite-element analyses (FEA). The effects of different analysis parameters and finite-element types on the thermo-mechanical properties were analyzed. With the results of the FEA we determined the deformations to the headlamp housing. This analysis helped us to eliminate the causes of the bad sealing between the housing and the cover of the headlamp.
Keywords: žarometi; obremenitve temperaturne; stanja napetostno-deformacijska; metode končnih elementov; trdnost; temperaturni profil; finite element method; metoda končnih elementov